Accounting research training: from statement to action (2014)
Accounting research has been thought as the basis of political subject formation. Nevertheless, researching remains as a marginal activity in the field, which is interpreted as the result of the didactics applied to its teaching. This article aims at understanding the educational intentions expressed through descriptive programs of research training courses and teaching methodologies. A qualitative analysis of them is developed by contrasting them with Wolgfang Klafki’s didactics theory and the accounting research training backgrounds published in Colombia. It was found that, although from the theoretical formation areas the need of a critical formation is recognized, in the methodological formation areas this idea becomes diluted. Likewise, from the teaching resources viewpoint, no actions ensure the achievement of the stated objectives.